PEMBANGUNAN EKONOMI NASIONAL - Silitonga, Arino Fanther; Jhon Kristopel Manalu; Remus Silalahi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Economic development is a multidimensional process aimed at increasing a society's per capita income while simultaneously realizing fundamental changes in a country's economic structure, shifting from traditional to modern sectors. This journal aims to analyze the determinant factors influencing the success of economic development, focusing on the intervention of fiscal and monetary policies and the role of sustainable development in developing countries. This research employs a literature study method with a descriptive qualitative approach, reviewing various scientific sources such as development economics textbooks and accredited journal articles. The findings indicate that the success of economic development is not only measured by gross domestic product growth (quantitative aspect) but also by social indicators such as the Quality of Life Index, income distribution, and the enhancement of human resource capacity. Furthermore, the implementation of the sustainable development concept is found to be crucial to ensuring that current economic improvements do not compromise the needs of future generations. In conclusion, the synergy between well-targeted economic policies, institutional strengthening, and active community participation are essential prerequisites for achieving inclusive and sustainable economic development.